THE CONDITION OF THE PERIODONTAL TISSUES IN CHILDREN WITH DELAYED TEETH ERUPTION - Horokhovskyi, V.V.; Schnayder, S.A.; Shchepanskyy, F.Y.; Borodach, V.O.; Pyndus, V.B. (World of Medicine and Biology, 2021)
The study of the periodontal tissues in children with delayed teeth eruption is of significant scientific and practical interest and an urgent task for dentistry. A survey of 124 children of 7 and 8 years of both sexes was conducted and comprehensive study of the periodontal tissues was performed in this children. The results of the studies indicate a high prevalence and intensity of the periodontal tissue diseases in the children 7 and 8 years old with delayed teeth eruption. As a result, a high need for children with delayed teeth eruption in the treatment of inflammatory diseases of the periodontal tissues and the need of developing a therapeutic and preventive complex for this category of children were identified.
Keywords: gingivitis; delayed teeth eruption; oral health; survey; children